Risk factors and molecular epidemiology of colonizing carbapenem-resistant Enterobacterales in pediatric inpatient in Shenzhen, China - Hongmei Yang; Zhile Xiong; Ke Cao; Yunxing He; Songhong Song; Fangjun Lan; Kaiyue Yang; Xiaochun Liu; Chaohui Duan; Zhenwen Zhou (Journal of Infection and Public Health)
Objectives: The spread of CRE has been rapid on a global scale and represents a significant challenge in nosocomial infections worldwide. The aim is to evaluate the risk factors for CRE colonization and to describe the molecular and clinical characteristics of CRE colonization in pediatric inpatients in Shenzhen, China. Methods: We collected stool specimens from 2474 randomly selected pediatric inpatient hospitalized in 2 pediatric hospitals in Shenzhen between January 2023 and December 2023 for subsequent microbiological analysis, including microbial culture, species identification, antimicrobial sensitivity testing, genetic characterization and multilocus sequence typing (MLST). In addition, we conducted a case-control study to identify potential risk factors for gastrointestinal CRE colonization. Results: Of the 2474 non-replicating pediatric stool specimens collected, 3.6 % (n = 90) test positive for CRE. The most dominant CRE species were Escherichia coli (n = 67, 74.5 %), and Klebsiella pneumoniae (n = 17, 19.0 %). Multidrug resistance and carbapenemase production were observed in most CRE isolates. In CR E. coli and CR K. pneumoniae, the blaNDM was the predominant resistance gene, accounting for 95.5 % and 76.5 %, respectively. MLST showed considerable clonal diversity among the CR E. coli and CR K. pneumoniae isolates and the most common ST in CR E. coli was ST48 (n = 6, 9.0 %) and ST35 in CR K. pneumoniae (n = 4, 23.5 %). Conclusions: This study once again shows that pediatric inpatients in South China were colonized by a diversity of CRE strains, increasing the likelihood of difficult-to-treat infections. Hospitals and competent authorities should take appropriate public health measures, to prevent the further spread of CRE.